Acute Peritonitis: A Rare Complication Revealing Intestinal Tuberculosis - Sabbah.M; Trad.D; Jemmali.C; Jouini R; Elloumi H; Bibani.N; Ouakaa.A; Gargouri.D (Journal of Spleen And Liver Research, 2019)
Intestinal tuberculosis diagnosis is often difficult because of non-specific symptoms, miming many other conditions such as malignancy, infectious disease, and inflammatory bowel disease. Free intestinal perforation is an uncommon but life-threatening complication of intestinal tuberculosis, associated with high morbidity and mortality.
Keywords: Intestinal tuberculosis diagnosis